Efecto de la solución acuosa del tarwi (Lupinus mutabilis) en el control de la helmintiasis en ovinos del distrito de baños Provincia de Lauricocha - Apaestegui Livaque, Rosel (2017)
With the purpose of determining the effect in the sheep Helmenticida was used 2 types of solution: solution to (soak) and solution B (boiled) in 20 units of analysis for each solution; having seen the results. Likewise in the examination of stool stool is a priori determined a greater incidence of Strongyloides eggs (100 % ), followed by taeniasis, Moniezia 75 %, and Dictiocaulosis 37.5 %, Distomatosis 12.5 %. It was found the close correlation between weight of the units of analysis and the highest dose of solution B (boiled). Solutions A and B were used in dose per Os from 1 to 4 ml/ kg of pv. With the results that the solution to (soak) in the 4 experimental groups was not observed any control of the parasitic load measured through the stool examination. Solution B (boiled) showed in the 4 experimental groups a slight variation in the decrease in the egg count.